A rare case of centronuclear myopathy with DNM2 mutation: genotype-phenotype correlation - Amir Ghorbani Aghbolaghi; Mirna Lechpammer (University of São Paulo, 2017)
Centronuclear myopathy (CNM) is a group of rare genetic muscle disorders characterized by muscle fibers with centrally located nuclei. The most common forms of CNM have been attributed to X-linked recessive mutations in the MTM1 gene; autosomal-dominant mutations in the DNM2 gene-encoding dynamin-2, the BIN1 gene; and autosomal-recessive mutations in BIN1, RYR1, and TTN genes. Dominant CNM due to DNM2 mutations usually follows a mild clinical course with the onset in adolescence. Currently, around 35 mutations of the DNM2 gene have been identified in CNM; however, the underlying molecular mechanism of DNM2 mutation in the pathology of CNM remains elusive, and the standard clinical characteristics have not yet been defined. Here, we describe the case of a 17-year-old female who presented with proximal muscle weakness along with congenital anomalous pulmonary venous connection (which has not been described in previous cases of CNM), scoliosis, and lung disease without a significant family history. Her creatine kinase level was normal. Histology, special stains, and electron microscope findings on her skeletal muscle biopsy showed CNM with the characteristic features of a DNM2 mutation, which was later confirmed by next-generation sequencing. This case expands the known clinical and pathological findings of CNM with DNM2 gene mutation